Carbon nanotube composite electrode material and preparation method thereof
By depositing a composite electrode material with a high-conductive active material layer and a low-volume expansion coefficient passivation coating on the carbon nanotube matrix, the problems of low conductivity and unstable interface of solid-state battery electrode materials are solved, and the synchronous improvement of conductivity and stability are achieved.
Patent Information
- Application Number
- CN202411926335.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-11
AI Technical Summary
The electrode materials of existing solid-state batteries have problems of low conductivity and large volume at the interface between the solid-state electrolyte and the electrode materials, which affect the battery performance.
Using carbon nanotube composite electrode material, by depositing an active material layer and a passivation coating on the carbon nanotube matrix, the conductivity of the active material layer is higher than that of the passivation coating, and the volume expansion coefficient of the passivation coating is low, ensuring the stability of the interface between the electrode material and the electrolyte.
The conductivity and stability of the electrode material are improved, and a stable ion transmission channel is built, which enhances the energy density and cycling stability of the battery.
Smart Images

Figure CN119812254A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrode materials, and in particular to a carbon nanotube composite electrode material and a preparation method thereof. Background Art
[0002] In modern energy storage technology, battery performance is crucial to the battery life of electronic products, the mileage of electric vehicles, and the energy storage efficiency of power grids. However, high requirements for battery performance require higher battery energy density, cycle stability, and safety requirements. Among many batteries, although the commercialization of liquid lithium-ion batteries has been a great success, liquid lithium-ion batteries still have limitations in terms of energy density, cycle stability, and safety. Compared with liquid lithium-ion batteries, solid-state batteries have attracted much attention for their advantages of high safety, high energy density, and high cycle stability. However, solid-state batteries still face problems with the interface between solid electrolytes and electrode materials. These problems will not only make the ionic conductivity of the electrode materials of solid-state batteries lower, but also lead to a larger volume of electrode materials for solid-state batteries, and a larger volume of electrode materials will affect the battery performance of solid-state batteries.
[0003] Although functional layers can be covered on the surface of electrode materials to improve their conductivity and theoretical capacitance, most of these materials are difficult to improve the interface problems between solid electrolytes and electrode materials, and these functional layers will affect the stability of electrode materials during normal working stages. Summary of the invention
[0004] The present application provides a carbon nanotube composite electrode material and a preparation method thereof to solve the following technical problem: how to simultaneously improve the conductivity and stability of the electrode material.
[0005] In the first aspect, the present application provides a carbon nanotube composite electrode material, which includes a carbon nanotube matrix and an active material layer and a passivation coating sequentially covering the surface of the carbon nanotube matrix, wherein the conductivity of the active material layer is greater than the conductivity of the passivation coating, the volume expansion coefficient of the passivation coating is less than the volume expansion coefficient of the active material layer; and the thickness of the active material layer is greater than the thickness of the passivation coating.
[0006] Optionally, the thickness of the active material layer is 5 nm to 20 nm; and / or
[0007] The thickness of the passivation coating is 2nm-10nm.
[0008] Optionally, the active material layer includes ZnO and / or LiCoO2;
[0009] The passivation coating includes at least one of: Al2O3, ZrO2, HfO2 and TiO2.
[0010] In a second aspect, the present application provides a method for preparing the composite electrode material according to the first aspect, the method comprising:
[0011] Under the condition of inert gas, a carbon nanotube matrix and a first precursor containing an active material are subjected to a first atomic layer deposition to obtain a composite matrix containing an active material layer;
[0012] Under the condition of inert gas, a second precursor containing a passivation material and the composite substrate are subjected to a second atomic layer deposition to obtain a coarse-grade composite electrode material containing a passivation coating and an active material layer.
[0013] Optionally, the first precursor includes diethyl zinc and first deionized water, and the introduction time t1 of the diethyl zinc and the introduction time t2 of the first deionized water satisfy the relationship: t1:t2≥5:2.
[0014] Optionally, the second precursor includes trimethylaluminum and second deionized water, and the introduction time t3 of the trimethylaluminum and the introduction time t4 of the second deionized water satisfy the relationship: t3:t4≥1:1.
[0015] Optionally, the temperatures of the first atomic layer deposition and the second atomic layer deposition are both 100° C. to 200° C., and the pressures of the first atomic layer deposition and the second atomic layer deposition are less than 0.1 torr.
[0016] Optionally, the inert gas is introduced for 40s to 60s.
[0017] Optionally, the second precursor containing the passivation material and the composite substrate are subjected to a second atomic layer deposition under an inert gas condition to obtain a composite electrode material containing a passivation coating and an active material layer, and then comprises:
[0018] The coarse-grade composite electrode material is annealed to obtain a composite electrode material.
[0019] Optionally, the temperature of the annealing treatment is ≤550°C.
[0020] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0021] The embodiment of the present application provides a carbon nanotube composite electrode material. The carbon nanotube composite electrode material uses carbon nanotubes as a matrix. Based on the porous structure of the carbon nanotubes, a complex conductive network can be formed to improve the electronic conductivity of the composite electrode material. In addition, an active material layer and a passivation coating are deposited on the surface of the carbon nanotubes. The active material layer can be deposited on the surface of the conductive network formed by the carbon nanotubes. Based on the characteristic that the conductivity of the active material layer is greater than the conductivity of the passivation coating, the conductivity of the carbon nanotubes can be further improved by the high conductivity of the active material. In addition, based on the characteristic that the volume expansion coefficient of the passivation coating is less than the volume expansion coefficient of the active material layer, the passivation coating has a smaller deformation space when the composite electrode material is working, so as to suppress the volume expansion of the active material layer when the composite electrode material is working. Thereby improving the interface stability between the electrode material and the electrolyte; in addition, the thickness of the active material layer is greater than the thickness of the passivation coating, so that the composite electrode material has an active material layer and a passivation coating of sufficient thickness. The active material layer of sufficient thickness can store more charge, thereby improving the energy density of the battery, and the passivation coating of sufficient thickness can not only stabilize the interface stability between the electrode material and the electrolyte, but also can improve the conductivity of the composite electrode material without affecting the transmission of lithium ions and the rate performance of the battery, thereby simultaneously improving the conductivity and stability of the electrode material; therefore, the composite electrode material can construct a stable ion transmission channel in the composite electrode material through the interaction of the carbon nanotube matrix, the active material layer and the passivation coating, and can also improve the stability and of the composite electrode material without sacrificing the battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0024] Figure 1 A schematic diagram of the structure of a carbon nanotube composite electrode material provided in an embodiment of the present application;
[0025] Figure 2 A schematic diagram of the main flow of a method for preparing the composite electrode material provided in an embodiment of the present application;
[0026] Figure 3 A schematic flow chart of a method for preparing the composite electrode material provided in an embodiment of the present application. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0028] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited number (fractional or integer) within the indicated range.
[0029] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions, refers to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond to the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C
[0030] =1:2:3.
[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this article can be purchased from the market or prepared by existing methods.
[0032] Figure 1 The schematic diagram of the structure of a carbon nanotube composite electrode material provided in an embodiment of the present application is exemplarily shown;
[0033] like Figure 1 As shown, an embodiment of the present application provides a carbon nanotube composite electrode material, which includes a carbon nanotube matrix and an active material layer and a passivation coating sequentially covering the surface of the carbon nanotube matrix, wherein the conductivity of the active material layer is greater than the conductivity of the passivation coating, the volume expansion coefficient of the passivation coating is less than the volume expansion coefficient of the active material layer; and the thickness of the active material layer is greater than the thickness of the passivation coating.
[0034] It should be noted that the carbon nanotube composite electrode material provided in the embodiment of the present application has significant advantages and characteristics. The carbon nanotube composite electrode material constructs a stable ion transmission channel through the interaction of the carbon nanotube matrix, the active material layer and the passivation coating, and simultaneously improves the conductivity and stability of the electrode material. The core points include:
[0035] (1) Carbon nanotube matrix:
[0036] Using carbon nanotubes as the matrix, the porous structure of the nanotubes forms a complex conductive network. This structure effectively improves the electronic conductivity of the composite electrode material and provides a basis for the efficient operation of the battery.
[0037] (2) Deposition of active material layer and passivation coating:
[0038] An active material layer is deposited on the surface of the carbon nanotubes, and the active material layer has a higher conductivity than the passivation coating. This property further improves the conductivity of the carbon nanotubes and helps to quickly transfer charges during the battery charging and discharging process. At the same time, the deposited passivation coating has a low volume expansion coefficient, which can inhibit the volume expansion of the active material layer when the composite electrode material is working. This helps to maintain the interface stability between the electrode material and the electrolyte and extend the service life of the battery.
[0039] (3) Layer thickness design:
[0040] The thickness of the active material layer is greater than that of the passivation coating. This design enables the composite electrode material to have a sufficiently thick active material layer to store more charge, thereby increasing the energy density of the battery. A sufficiently thick passivation coating not only stabilizes the interface between the electrode material and the electrolyte, but also ensures the smooth transmission of lithium ions and the unaffected rate performance of the battery.
[0041] (4) Comprehensive performance improvement:
[0042] Through the above design, the composite electrode material maintains high conductivity while significantly improving stability. This comprehensive performance improvement enables the battery to more efficiently transfer ions and charges during the charging and discharging process, thereby improving the overall performance of the battery.
[0043] In addition, this composite electrode material constructs a stable ion transmission channel by optimizing the structure and interaction of each layer without sacrificing battery performance, providing strong support for the long life and high performance of the battery.
[0044] In summary, the embodiments of the present application provide a carbon nanotube composite electrode material, which achieves simultaneous improvement of conductivity and stability through clever layer structure design and material selection, and provides new ideas and methods for the development of battery technology.
[0045] In some optional embodiments, the thickness of the active material layer is 5 nm to 20 nm; and / or
[0046] The thickness of the passivation coating is 2nm to 10nm;
[0047] In these embodiments, the thickness of the active material layer can be 5nm to 20nm, so that the composite electrode material has an active material layer of sufficient thickness. The active material layer of sufficient thickness can store more charges to improve the energy density of the battery. In addition, the active material layer of sufficient thickness will not excessively affect the transmission of lithium ions and the rate performance of the composite electrode material, so that the active material layer has a higher conductivity, thereby improving the conductivity of the composite electrode material; in addition, the thickness of the passivation coating can be 2nm to 10nm, so that the passivation coating has a sufficient thickness. The passivation coating of sufficient thickness can effectively inhibit the volume expansion of the active material layer during the operation of the composite electrode material, and at the same time does not affect the transmission of lithium ions and the rate performance of the battery, thereby improving the interface stability between the electrode material and the electrolyte.
[0048] The thickness of the active material layer may be 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, or 20 nm.
[0049] The thickness of the passivation coating may be 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.
[0050] In some optional embodiments, the active material layer includes ZnO and / or LiCoO2;
[0051] The passivation coating comprises at least one of: Al2O3, ZrO2, HfO2 and TiO2;
[0052] In these embodiments, the active material layer may include ZnO and / or LiCoO2, so that the active material layer has a higher theoretical capacitance, so that the composite electrode material has a higher energy density; in addition, the active material layer also has more lithium ion transmission channels, so that the active material layer has a higher conductivity; in addition, the passivation coating may include at least one of Al2O3, ZrO2, HfO2 and TiO2, so that the passivation coating can effectively inhibit the volume expansion of the composite electrode material of the active material layer during operation, and at the same time does not affect the transmission of lithium ions and the rate performance of the battery, thereby improving the interface stability between the electrode material and the electrolyte.
[0053] The active material layer may be ZnO, LiCoO2, or a mixture of ZnO and LiCoO2.
[0054] The passivation coating may be Al2O3, ZrO2, HfO2, or TiO2.
[0055] Figure 2 A schematic diagram of the main process of a method for preparing the composite electrode material provided in an embodiment of the present application is exemplarily shown;
[0056] Based on a general inventive concept, such as Figure 2 As shown, the embodiment of the present application provides a method for preparing the composite electrode material, the method comprising:
[0057] S1. Under inert gas conditions, a carbon nanotube substrate and a first precursor containing an active material are subjected to a first atomic layer deposition to obtain a composite substrate containing an active material layer;
[0058] S2. Under inert gas conditions, subjecting the second precursor containing the passivation material and the composite substrate to a second atomic layer deposition to obtain a coarse-grade composite electrode material containing a passivation coating and an active material layer.
[0059] This method is a method for preparing the above-mentioned composite electrode material. The specific composition and structure of the composite electrode material can refer to the above-mentioned embodiment. Since this method adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.
[0060] It should be noted that the inert gas may be nitrogen.
[0061] It should be noted that the carbon nanotube substrate may be pretreated before use, and the pretreatment methods may be cleaning and drying to ensure that the surface of the carbon nanotube substrate is clean and provide a good carbon nanotube substrate for subsequent coating.
[0062] In some optional embodiments, the first precursor includes diethyl zinc and first deionized water, and the introduction time t1 of the diethyl zinc and the introduction time t2 of the first deionized water satisfy the relationship: t1:t2≥5:2;
[0063] In these embodiments, the first precursor may include diethyl zinc and first deionized water, and the introduction time t1 of diethyl zinc and the introduction time t2 of the first deionized water may satisfy the relationship: t1:t2≥5:2, thereby promoting the full reaction of diethyl zinc and the first deionized water, and forming a zinc oxide active material layer of sufficient thickness on the surface of the carbon nanotube matrix. The active material layer of sufficient thickness can improve the energy density of the battery, and will not excessively affect the transmission of lithium ions and the rate performance of the composite electrode material, so that the active material layer has a higher conductivity, thereby improving the conductivity of the composite electrode material.
[0064] It should be noted that the introduction time t1 of the diethyl zinc may be 0.05 s, and the introduction time t2 of the first deionized water may be 0.02 s.
[0065] In some optional embodiments, the second precursor includes trimethylaluminum and second deionized water, and the introduction time t3 of the trimethylaluminum and the introduction time t4 of the second deionized water satisfy the relationship: t3:t4≥1:1;
[0066] In these embodiments, the second precursor may include trimethylaluminum and a second deionized water, and the introduction time t3 of trimethylaluminum and the introduction time t4 of the second deionized water may satisfy the relationship: t3:t4≥1:1, thereby promoting the trimethylaluminum and the second deionized water to react fully and forming an aluminum oxide passivation coating of sufficient thickness on the surface of the active material layer. The passivation coating of sufficient thickness can effectively inhibit the volume expansion of the active material layer during the operation of the composite electrode material without affecting the transmission of lithium ions and the rate performance of the battery, thereby improving the interface stability between the electrode material and the electrolyte.
[0067] It should be noted that the introduction time t3 of the trimethylaluminum can be 0.02 s, and the introduction time t4 of the second deionized water can be 0.02 s.
[0068] In some optional embodiments, the temperature of the first atomic layer deposition and the second atomic layer deposition are both 100° C. to 200° C., and the pressure of the first atomic layer deposition and the second atomic layer deposition is less than 0.1 torr;
[0069] In these embodiments, the temperature of the first atomic layer deposition and the second atomic layer deposition can be 100°C to 200°C, and the pressure of the first atomic layer deposition and the second atomic layer deposition can be less than 0.1 torr, so that the first atomic layer deposition and the second atomic layer deposition are fully carried out to obtain an active material layer and a passivation coating of sufficient thickness. Through the interaction between the carbon nanotube matrix, the active material layer and the passivation coating, a stable ion transport channel can be constructed in the composite electrode material. In addition, without sacrificing battery performance, the stability and of the composite electrode material can be improved.
[0070] The temperature of the first atomic layer deposition and the second atomic layer deposition may be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C.
[0071] In some optional embodiments, the inert gas is introduced for 40s to 60s;
[0072] In these embodiments, the inert gas may be introduced for 40s to 60s, so that the inert gas can be effectively introduced during the first atomic layer deposition and the second atomic layer deposition stages to facilitate the formation of the active material layer and the passivation coating.
[0073] The inert gas introduction time can be 40s, 45s, 50s, 55s or 60s.
[0074] Figure 3 A schematic flow chart of a method for preparing the composite electrode material provided in an embodiment of the present application is exemplarily shown;
[0075] In some optional embodiments, such as Figure 3 As shown, the second precursor containing the passivation material and the composite substrate are subjected to a second atomic layer deposition under the condition of an inert gas to obtain a composite electrode material containing a passivation coating and an active material layer, and then includes:
[0076] S3. annealing the coarse composite electrode material to obtain a composite electrode material;
[0077] In these embodiments, the coarse-grade composite electrode material is subjected to annealing treatment, which can promote further shaping of the active material layer and the passivation coating to obtain a passivation coating and an active material layer with sufficient thickness.
[0078] In some optional embodiments, the temperature of the annealing treatment is ≤550°C;
[0079] In these embodiments, the annealing temperature is ≤550°C, which promotes further shaping of the active material layer and the passivation coating to obtain a passivation coating and an active material layer of sufficient thickness; in addition, the annealing can also optimize the crystal morphology of the active material layer to further promote further shaping of the active material layer and the passivation coating, and facilitate the removal and embedding of lithium ions.
[0080] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples where specific conditions are not specified are usually measured in accordance with national standards / industry standards; if there are no corresponding national standards / industry standards, they are measured in accordance with common international standards, conventional conditions or conditions recommended by the manufacturer.
[0081] Example 1
[0082] like Figure 3 As shown, a method for preparing a composite electrode material comprises:
[0083] S1. Under inert gas conditions, a carbon nanotube substrate and a first precursor containing an active material are subjected to a first atomic layer deposition to obtain a composite substrate containing an active material layer;
[0084] S2. Under inert gas conditions, a second precursor containing a passivation material and a composite substrate are subjected to a second atomic layer deposition to obtain a coarse-grade composite electrode material containing a passivation coating and an active material layer;
[0085] S3. Annealing the coarse-grade composite electrode material to obtain a composite electrode material.
[0086] The thickness of the active material layer is 10 nm;
[0087] The thickness of the passivation coating was 5 nm.
[0088] The active material layer includes ZnO;
[0089] The passivation coating is Al2O3.
[0090] The first precursor includes diethyl zinc and first deionized water, and the introduction time t1 of diethyl zinc and the introduction time t2 of the first deionized water satisfy the relationship: t1:t2=5:2; the introduction time t1 of diethyl zinc is 0.05s, and the introduction time t2 of the first deionized water is 0.02s. The specific introduction time distribution is: (0.05s diethyl zinc + 30s nitrogen + 0.02s deionized water + 30s nitrogen)×100 rounds.
[0091] The second precursor includes trimethylaluminum and second deionized water, and the introduction time t3 of trimethylaluminum and the introduction time t4 of the second deionized water satisfy the relationship: t3:t4=1:1; the introduction time t3 of the trimethylaluminum is 0.02s, and the introduction time t4 of the second deionized water is 0.02s. The specific introduction time distribution is: (0.02s trimethylaluminum + 20s nitrogen + 0.02s deionized water + 20s nitrogen) × 50 rounds.
[0092] The temperature of the first atomic layer deposition is 100° C., and the pressure of the first atomic layer deposition is less than 0.1 torr.
[0093] The temperature of the second atomic layer deposition is 200° C., and the pressure of the second atomic layer deposition is less than 0.1 torr.
[0094] The annealing temperature is 300°C and the annealing time is 2h.
[0095] Example 2
[0096] Based on the contents disclosed in Example 1, the following modifications are further made:
[0097] The thickness of the active material layer is 5 nm;
[0098] The thickness of the passivation coating was 2 nm.
[0099] Example 3
[0100] Based on the contents disclosed in Example 1, the following modifications are further made:
[0101] The thickness of the active material layer is 20 nm;
[0102] The thickness of the passivation coating was 10 nm.
[0103] Example 4
[0104] Based on the contents disclosed in Example 1, the following modifications are further made:
[0105] The active material layer is LiCoO2;
[0106] The passivation coating is ZrO2.
[0107] The temperature of the first atomic layer deposition is 110° C., and the pressure of the first atomic layer deposition is less than 0.1 torr.
[0108] The temperature of the second atomic layer deposition is 180° C., and the pressure of the second atomic layer deposition is less than 0.1 torr.
[0109] Example 5
[0110] Based on the contents disclosed in Example 1, the following modifications are further made:
[0111] The active material layer is ZnO;
[0112] The passivation coating is TiO2.
[0113] The temperature of the first atomic layer deposition is 100° C., and the pressure of the first atomic layer deposition is less than 0.1 torr.
[0114] The temperature of the second atomic layer deposition is 160° C., and the pressure of the second atomic layer deposition is less than 0.1 torr.
[0115] Comparative Example 1
[0116] Based on the contents disclosed in Example 1, the following modifications are further made:
[0117] Instead of using a carbon nanotube matrix, the electrode material of the ZnO nanoplate battery is used directly.
[0118] Comparative Example 2
[0119] Based on the contents disclosed in Example 1, the following modifications are further made:
[0120] No passivation coating is used.
[0121] Comparative Example 3
[0122] Based on the contents disclosed in Example 1, the following modifications are further made:
[0123] A silicon substrate is used instead of a carbon nanotube substrate.
[0124] Comparative Example 4
[0125] Based on the contents disclosed in Example 1, the following modifications are further made:
[0126] The thickness of the passivation coating layer is greater than the thickness of the active material layer. The thickness of the passivation coating layer is 15 nm, and the thickness of the active material layer is 5 nm.
[0127] Related experiments and effect data:
[0128] 1. The composite electrode materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 were respectively assembled into double-electrode button cells, and the performance of these double-electrode button cells was tested. The test voltage range was 2.5V to 4.0V, and then a cycle stability test was performed. The cycle was repeated for 100 times and the capacity change was recorded. At the same time, a rate performance test was performed to test the charge and discharge capacity at different current densities. The results are shown in Table 1.
[0129] Table 1 Performance test results of double-electrode button cells of Example 1 and Comparative Example 1
[0130]
[0131] Combined with the experiment in Table 1, the discharge / charge capacity of the double-electrode button cell of Comparative Example 1 decreased to 478 mAh / g after 50 cycles;
[0132] In the first 10 cycles, the discharge / charge capacity of the dual-electrode button cell of Comparative Example 2 gradually decreased to 602 / 436 mAh / g, and after 50 cycles, there was no further loss of the discharge / charge capacity; in the first 150 cycles, the discharge / charge capacity of the dual-electrode button cell of Example 1 gradually decreased to 764 / 636 mAh / g, and there was no decrease in the discharge / charge capacity in the first 50 cycles.
[0133] 2. The composite electrode materials obtained in each embodiment and comparative example were assembled into double-electrode button cells, and the third discharge / charge capacity and the number of cycles at which the discharge / charge capacity began to decrease of these double-electrode button cells were tested. The results are shown in Table 2.
[0134] Table 2 Performance test results of double-electrode button cells of various embodiments and comparative examples
[0135]
[0136] It can be seen from Table 1 that the use of different active material layers has a greater impact on the discharge / charge capacity of the two-electrode button battery. This is because the conductivity of LiCoO2 is greater than that of ZnO, so its third discharge / charge capacity is better than that of other embodiments; in addition, if the thickness of the active material layer is greater than that of the passivation coating, its discharge / charge capacity will decrease significantly. This may be because the thickness of the active material layer is larger, resulting in interface instability in the two-electrode button battery.
[0137] In addition, if the carbon nanotube matrix is replaced with a traditional silicon matrix, the discharge / charge capacity of the two-electrode button battery will be greatly reduced, which shows that the carbon nanotube matrix has a significant improvement in the conductivity of the two-electrode button battery.
[0138] In summary, the embodiments of the present application provide a carbon nanotube composite electrode material, which achieves simultaneous improvement of conductivity and stability through clever layer structure design and material selection, and provides new ideas and methods for the development of battery technology.
[0139] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown in the present application, but will conform to the widest range consistent with the principles and novel features applied for by the present application.
Claims
1. A carbon nanotube composite electrode material, comprising a carbon nanotube substrate and an active material layer and a passivation coating sequentially covering the surface of the carbon nanotube substrate, wherein the conductivity of the active material layer is greater than the conductivity of the passivation coating, the volume expansion coefficient of the passivation coating is less than the volume expansion coefficient of the active material layer; and the thickness of the active material layer is greater than the thickness of the passivation coating.
2. The composite electrode material according to claim 1, wherein the thickness of the active material layer is 5 nm to 20 nm; and / or The thickness of the passivation coating is 2nm-10nm.
3. The composite electrode material according to claim 1, wherein the active material layer comprises ZnO and / or LiCoO2; The passivation coating includes at least one of: Al2O3, ZrO2, HfO2 and TiO2.
4. A method for preparing the composite electrode material according to any one of claims 1 to 3, the method comprising: Under the condition of inert gas, a carbon nanotube matrix and a first precursor containing an active material are subjected to a first atomic layer deposition to obtain a composite matrix containing an active material layer; Under the condition of inert gas, a second precursor containing a passivation material and the composite substrate are subjected to a second atomic layer deposition to obtain a coarse-grade composite electrode material containing a passivation coating and an active material layer. 5 . The method according to claim 4 , wherein the first precursor comprises diethyl zinc and first deionized water, and the introduction time t1 of the diethyl zinc and the introduction time t2 of the first deionized water satisfy the relationship: t1:t2≥5:
2.
6. The method according to claim 4, wherein the second precursor comprises trimethylaluminum and second deionized water, and an introduction time t3 of the trimethylaluminum and an introduction time t4 of the second deionized water satisfy the relationship: t3:t4≥1:
1. 7 . The method according to claim 4 , wherein the temperatures of the first atomic layer deposition and the second atomic layer deposition are both 100° C. to 200° C., and the pressures of the first atomic layer deposition and the second atomic layer deposition are less than 0.1 torr.
8. The method according to claim 4, wherein the inert gas is introduced for 40s to 60s.
9. The method according to claim 4, wherein the second precursor containing the passivation material and the composite substrate are subjected to a second atomic layer deposition under an inert gas condition to obtain a composite electrode material containing a passivation coating and an active material layer, and then comprises: The coarse-grade composite electrode material is annealed to obtain a composite electrode material. 10 . The method according to claim 9 , wherein the temperature of the annealing treatment is ≤550° C.